Los menores extranjeros no acompañados: doble condición, doble victimización = Unaccompanied foreign minors : doble condition, doble victimization - Salinas, Ane Viana (Revista de victimología, 2023)
Unaccompanied foreign minors are a group with a particular legal situation, as they are subject to two different legal statuses: on the one hand, they are minors, considered as subjects of rights and protection, and on the other hand, they are foreigners from third countries, subject to control and expulsion. However, the status of foreigners is prioritised over that of minors, so that situations of stigmatisation and victimization are not very visible. The aim of this article is to explore victimologically the situations of victimization suffered by unaccompanied foreign minors under the protection of the Provincial Council of Gipuzkoa. In addition, to ratify how the double condition they present is closely linked to a double victimisation: child and youth victimization, on the one hand; and migrant victimization or racist victimisation, on the other hand.